Pārati iyal : collection of research papers on Bharathi - Iṉṉāci, Cū., 1934- (Āyvu Maiyam, Tamiḻ Mutukalait Tuṟai, Tūya Cavēriyār Kallūri : Viṟpaṉai urimai, Vaḷaṉaruḷ Veḷiyīṭu, 1982)
Research papers on Pāratiyār, 1882-1921, Tamil litteateur and Indian freedom fighter.